FERGHANA VALLEY ON THE EVE OF THE FORMATION OF THE KOKAND KHANATE (Scientific journal of the Fergana State University, 2024)
This article examines the political history of the Fergana Valley in the late 17th and early 18th centuries through written sources and academic literature. Due to the limited coverage of the region's political situation during this period in the sources, preliminary scientific conclusions have been drawn based on the description of the political processes that occurred during this time.